Applying AI-enhanced digital games in teaching English vocabulary - Ahmed, Fawzi Eltayeb Yousuf; Ali, Elsadig Hussein Fadlalla; Usmani, Saima; Kottaparamban, Musadhique; Ibrahim, Mohammed Ali El-Siddig; Hamed, Fatima Mohamed Ali; Abdallah, Nawal Mosa Mohammed (Research Journal in Advanced Humanities, 2026)
The current study examines the perspectives of EFL university teachers regarding the application of AI-enhanced digital games in teaching English vocabulary. This study was conducted in the first semester of the 2025-2026 academic year. It examines the challenges that EFL university teachers encounter when utilizing AI-enhanced digital games in vocabulary instruction and the suggestions they offer for overcoming them. To achieve these objectives, the study employs two tools for data collection: a questionnaire and a structured interview. The questionnaire targets 60 EFL teachers at various Saudi universities. Moreover, ten experienced teachers are selected to respond to the interview questions. Data analysis of both the questionnaire and the interview indicates that teachers have positive attitudes about using AI-enhanced games in teaching English vocabulary. They view AI-enhanced digital games as a successful teaching method for enhancing student motivation and engagement by promoting a sense of autonomy and competence. The findings further demonstrate the importance of AI-enhanced games in transforming conventional learning activities into engaging and interactive experiences. The findings also indicate that teachers face numerous obstacles when attempting to use these games, including technical difficulties, inadequate training, a lack of technological proficiency, and insufficient time for students to interact with one another. Given these challenges, the study recommends offering teachers a brief training workshop on these AI-enhanced games or tools prior to their implementation. It also proposes providing ongoing technical support, allocating time for teachers’ development and experimentation with tools, and incorporating evaluation standards to assess the impact of educational games on both short- and long-term student outcomes.